2017
DOI: 10.1016/j.marpetgeo.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Systematic vertical and lateral changes in quality and time resolution of the macrofossil record: Insights from Holocene transgressive deposits, Po coastal plain, Italy

Abstract: 2017-08-25T16:28:25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Previous studies established that there are predictable changes, both in the quality of preservation and the temporal resolution, in the fossil record along a depositional profile (Scarponi et al . , ). However, that contradict those of previous studies were observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies established that there are predictable changes, both in the quality of preservation and the temporal resolution, in the fossil record along a depositional profile (Scarponi et al . , ). However, that contradict those of previous studies were observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has never been directly tested, except in a succession of transgressive/regressive deltaic systems (Scarponi et al . ).…”
Section: Confounding Variables: Measures Of Unpredictabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of molluscs related to nearshore environments, such as N. olla, reinforce this interpretation. In the middle part (homogeneous sandy siltstone), olygotypic macrobenthic assemblages dominated by C. gibba or T. tricarinata (Bks 2, 6) point toward shallow marine settings under high sedimentary inputs (e.g., prodelta to distal delta front deposits; [13,14,15]). Within this unit, the transition to sandy bodies, usually devoid of fossils (Bk 8), is consistent with increasing sedimentation rates.…”
Section: Siliciclastic: Vigoleno Castle Sectionmentioning
confidence: 99%